2011
DOI: 10.1080/10570314.2010.536964
|View full text |Cite
|
Sign up to set email alerts
|

Socializing Messages in Blue-Collar Families: Communicative Pathways to Social Mobility and Reproduction

Abstract: This study explicitly links processes of anticipatory socialization to social mobility and reproduction. An examination of the socializing messages exchanged between blue-collar parents (n = 41) and their children (n = 25) demonstrate that family-based messages about work and career seldom occur in straightforward, unambiguous ways. Instead, messages take several paths (direct, indirect, ambient, and omission). Further, the content of messages communicated along these paths often is contradictory. That is, son… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 29 publications
1
40
0
Order By: Relevance
“…Although these elements of socialization may manifest prior to entry, research has yet to fully explore what constitutes socialization that occurs in anticipatory socialization. Past research has shown that prior experiences, like recruitment activities and even the messages we receive as children, socialize us into organizations and occupations (e.g., Buzzanell, Berkelaar, & Kisselburgh, 2011;Gabor, 2013;Hylmo, 2006;Levine & Hoffner, 2006;Lucas, 2011;Myers, Jahn, Gailliard, & Stoltzfus, 2011). However, we know little about how internships-a prevailing practice for most college-educated people entering the workforce today-contribute to organizational and vocational socialization.…”
Section: Study Rationalementioning
confidence: 91%
See 3 more Smart Citations
“…Although these elements of socialization may manifest prior to entry, research has yet to fully explore what constitutes socialization that occurs in anticipatory socialization. Past research has shown that prior experiences, like recruitment activities and even the messages we receive as children, socialize us into organizations and occupations (e.g., Buzzanell, Berkelaar, & Kisselburgh, 2011;Gabor, 2013;Hylmo, 2006;Levine & Hoffner, 2006;Lucas, 2011;Myers, Jahn, Gailliard, & Stoltzfus, 2011). However, we know little about how internships-a prevailing practice for most college-educated people entering the workforce today-contribute to organizational and vocational socialization.…”
Section: Study Rationalementioning
confidence: 91%
“…(Buzzanell et al, 2011, p. 160) Similarly, Lucas (2011) found that families communicate socializing messages about blue-collar work in complex, ambiguous, and even contradictory ways. Importantly, these studies and others (e.g., Saks & Ashforth, 1997) indicated that vocational anticipatory socialization messages occur through a variety of sources and message paths, not just direct memorable messages.…”
Section: Research In Vocational Anticipatory Socializationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although families may differ greatly in how members fulfill roles, societies usually expect family members to assist each other. First, families' career and work socialization assistance often takes the form of direct, indirect, and ambient messages embedded within more macro Discourses of economy, gender, class, and other forms of difference (Broadfoot et al, 2008;Dallimore, 2003;Gabor, 2009;Jablin, 1982Jablin, , 1985aJablin, , 1985bJablin, , 1987Jablin, , 2001Kuhn et al, 2008;Lucas, 2011). Second, socialization may be ongoing and/or anticipate occupational and educational choices.…”
Section: Families' Socialization Into Careersmentioning
confidence: 95%